The Real Transcending Itself (Through Love): Radical Solitude in the Heart of Love: Реалното коешто се трансцендира себе си (низ љубов): Радикална самотија во срцето на љубовта - Kolozova, Katerina; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Katerina Kolozova | Катерина Колозова Title (English): The Real Transcending Itself (Through Love): Radical Solitude in the Heart of Love Title (Macedonian): Реалното коешто се трансцендира себе си (низ љубов): Радикална самотија во срцето на љубовта Translated by (English to Macedonian): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 171-212 Page Count: 41 Citation (English): Katerina Kolozova, “The Real Transcending Itself (Through Love): Radical Solitude in the Heart of Love,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 171-212. Citation (Macedonian): Катерина Колозова, „Реалното коешто се трансцендира себе си (низ љубов): Радикална самотија во срцето на љубовта“, превод од англиски Родна Русковска, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 171-212.